Kepuasan Pelanggan Yang Dipengaruhi Servicescape, Lifestyle, Word of Mouth, dan Kualitas Pelayanan: Studi pada Bintang Army Jakarta - Bima Aji Bhaskara; Aris Budiono (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study aims to analyze whether there is a simultaneous and partial influence between the independent variables, namely Servicescape (X1), Lifestyle (X2), Word Of Mouth (X3), and Quality of Service (X4), on the dependent variable, namely Customer Satisfaction (Y), in the context of a company engaged in the sports shop. This study involved 78 respondents who filled out a questionnaire using the Likert scale method. Quantitative methods are used using multiple linear regression and SPSS 22 applications to analyze the effect simultaneously and partially. The results showed that simultaneously, the four independent variables, namely Servicescape, Lifestyle, Word of Mouth, and Service Quality, had an influence on the dependent variable, namely Customer Satisfaction. However, partially, there are three independent variables, namely Servicescape, Lifestyle, and Word Of Mouth, which have no significant effect on the dependent variable. Only the variable Service Quality has an effect on Customer Satisfaction at Bintang Army Jakarta.